Local Fixation of Colistin With Fibrin Spray: An in vivo Animal Study for the Therapy of Skin and Soft Tissue Infections - Janko, Maren; Dust, Fabian; Wagner, Pia Viktoria; Gurke, Robert; Frank, Johannes; Henrich, Dirk; Marzi, Ingo; Verboket, René Danilo (Frontiers in Surgery, 2022)
Objective: Skin and soft tissue infections (SSTI) are a commonly known entity of diseases associated with difficult treatment procedures. The current gold standard is radical surgical debridement accompanied by systemic antibiotic therapy. In clinical settings, local antibiotics alone or formulated within carrier material are commonly used alongside this therapy regimen. One possibility of local antibiotic application is the fixation of colistin with fibrin glue spray. It is not yet sufficiently researched how the local antibiotic concentrations remain as high as possible over time. Methods: We conducted an animal study including 29 male Wistar rats inducing sterile back sores reaching the muscle fascia. We sprayed only colistin, simultaneously or consecutively, with fibrin glue in different groups in order to measure the tissue concentration of the antibiotic applied locally. Results: After liquid chromatography and quadrupole mass spectrometry analysis, it could be demonstrated that in comparison to the colistin group, tissue concentrations of colistin stayed significantly higher in the wound tissue when it was fixed with fibrin glue. This was observed in both groups, the simultaneous as well as in the consecutively fibrin glue sprayed groups after colistin application. Conclusion: The fixation of colistin with the fibrin-glue-spray technique as a carrier for local antibiotic therapy is an easy and inexpensive method and shows promising potential for the treatment of SSTI.